Financial inclusion and farmers' income increase: Effects and realization mechanism. - Guibo Liu; Xiaoxian Gong; Guandong Wang (PLoS ONE)
From the perspective of agricultural industrialization, based on China's provincial data from 2006 to 2022, it studies the impact of financial inclusion on farmers' income. We have found that financial inclusion can effectively promote the growth of farmers' income, and this effect shows the heterogeneity of different income structures, income levels, and regional types. More importantly, agricultural industrialization is an important mechanism for financial inclusion to promote farmers' income growth. However, the interactive effect of financial inclusion and agricultural industrialization has not promoted the growth of farmers' income, indicating that there are certain structural problems in the current development of financial inclusion. We suggest that the development of financial inclusion should aim at the agricultural industrialization based on division of labor and cooperation. It can focus on supporting the development of local leading industries with regional comparative advantages, guide farmers to enter the agricultural industry chain, and improve farmers' opportunities to share economic results.